2020
DOI: 10.1111/jfd.13319
|View full text |Cite
|
Sign up to set email alerts
|

Immersion challenge of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. did not increase the severity of Neoparamoeba perurans‐induced amoebic gill disease (AGD)

Abstract: Amoebic gill disease (AGD) is one of the main health issues impacting farmed Atlantic salmon. Neoparamoeba perurans causes AGD; however, a diversity of other amoeba species colonizes the gills and there is little understanding of whether they are commensal or potentially involved in different stages of gill disease development. Here, we conduct in vivo challenges of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. to investigate their pathogenicity to Atlantic salmon gills. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The histopathological analysis revealed epithelial cell proliferation, secondary lamellar fusion, and the fusion or attachment of multiple lamellae, which are commonly reported symptoms when Atlantic salmon are infected with N. perurans [25,29,30,[69][70][71][72][73]. Moreover, according to English et al [73], in addition to the typical symptoms, inflammatory leukocytes were observed within the central venous sinuses, with squamous epithelial cells surrounding the inflamed lymphocytes, and basal infiltration was observed in some lymphocytes.…”
Section: Discussionmentioning
confidence: 92%
“…The histopathological analysis revealed epithelial cell proliferation, secondary lamellar fusion, and the fusion or attachment of multiple lamellae, which are commonly reported symptoms when Atlantic salmon are infected with N. perurans [25,29,30,[69][70][71][72][73]. Moreover, according to English et al [73], in addition to the typical symptoms, inflammatory leukocytes were observed within the central venous sinuses, with squamous epithelial cells surrounding the inflamed lymphocytes, and basal infiltration was observed in some lymphocytes.…”
Section: Discussionmentioning
confidence: 92%
“…In AGD cases, although N. perurans is regarded as the primary causative agent (Crosbie et al 2012 ), it is known that a range of other amoebae co-colonise the AGD-affected gill (English et al 2019 ). A pathogenic role for these other amoebae is unclear, however in vivo Atlantic salmon challenges with cultured parasite have suggested that they represent either normal eukaryotic gill fauna or opportunistic colonisation (English et al 2021 ). Further studies are required to confirm this finding in the context of natural disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main limitations of our study is the fact that results from glycan arrays and SPR analysis are based on a single N. perurans isolate. Even though the strain is still infective (English et al, 2021), it would be interesting to investigate whether variation in binding affinity to the same target receptor (by SPR analysis) would differ amongst strains with pathogenic variability. For instance, it has been reported for A. castellanii that the expression levels of MBP directly correlate with the virulence potential of isolates with different degrees of in vitro pathogenicity (Garate et al, 2006).…”
Section: Discussionmentioning
confidence: 99%